Analisis Penyelesaian Sengketa Kredit Bermasalah Melalui Mediasi: Studi Kasus Putusan Nomor 14/Pdt.G.S/2021/PN Kbm di Pengadilan Negeri Kebumen - Jayamahe, Moza Hadi Maheswara Kunto; Dewi W, Alicia Syahla (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims to analyse civil disputes arising from money lending and borrowing agreements with certificate collateral, especially in the context of Decision Number 14/Pdt.G.S/2021/PN Kbm. This research uses a normative juridical method, focusing on civil law that regulates lending and borrowing and land title collateral.The results show that defaults often occur when debtors do not fulfil debt payment obligations, which results in the execution of collateral by creditors. In this case, the certificate used as collateral does not always belong to the debtor, thus creating legal complexities related to ownership and land rights. The research also identifies the importance of legal protection for parties involved in credit agreements and the need for clarity in the agreement documents to prevent disputes in the future. The conclusion of this study emphasises that stricter regulation and a deeper understanding of the rights and obligations in credit agreements are necessary to reduce the risk of default and legal disputes.